2024
DOI: 10.1021/acs.analchem.3c03517
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Phosphatidylserine Molecules on the Surface of Individual Cells Using Single-Molecule Force Spectroscopy

Zhirong Li,
Lulu Zhang,
Zhanzhong Wang
et al.

Abstract: Identification of the phosphatidylserine (PS) discrepancies occurring on the cellular membrane during apoptotic processes is of the utmost importance. However, monitoring the quantity of PS molecules in real-time at a single-cell level currently remains a challenging task. Here, we demonstrate this objective by leveraging the specific binding and reversible interaction exhibited by the zinc(II) dipyridinamine complex (ZnDPA) with PS. Lipoic acid-functionalized ZnDPA (LP-ZnDPA) was subsequently immobilized onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…SERS detected a decrease in phospholipid-related spectral peaks after astrocyte activation, including phosphatidylserine at 524 cm − 1 , phosphatidylinositol at 776 cm − 1 , and phospholipids at 1745cm − 1 . Phosphatidylserine, an aminophospholipid located in the inner leaflet of the membrane, is closely related to inflammatory responses, oxidative stress, and apoptosis [ 44 ]. Previous reports have indicated that changes in phospholipids suggest alterations in the composition of glial cell membranes during neuroinflammation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…SERS detected a decrease in phospholipid-related spectral peaks after astrocyte activation, including phosphatidylserine at 524 cm − 1 , phosphatidylinositol at 776 cm − 1 , and phospholipids at 1745cm − 1 . Phosphatidylserine, an aminophospholipid located in the inner leaflet of the membrane, is closely related to inflammatory responses, oxidative stress, and apoptosis [ 44 ]. Previous reports have indicated that changes in phospholipids suggest alterations in the composition of glial cell membranes during neuroinflammation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%